The Implementation of Oral Presentation to Enhance Students’ Speaking Skills at Islamic University Jepara - Rizqi, Noviyanti Noor; Haryanto, Haryanto (Center of Language and Cultural Studies [CLCS], 2024)
The varied effects of oral presentations on students' speaking abilities and language learning are examined in this study. The research examines students' viewpoints and the difficulties they face during presenting sessions using thorough assessment criteria that cover accuracy, fluency, topic, and presentation. The results show that oral presentations are viewed by students as a useful method for expanding their vocabulary, comprehending the English language structure, and becoming more proficient overall. Even if some students struggle with confidence, they actively look for pertinent references to enhance the quality of their presentations. The study concludes that oral presentations have a major impact on how well pupils can talk. Future directions for research and instructional strategies are explored.